Gas exchange and photochemical efficiency of cotton cultivars under leaf application of silicon - Ferraz, Rener Luciano de Souza; Beltrão, Napoleão Esberard de Macêdo; Melo, Alberto Soares de; Magalhães, Ivomberg Dourado; Fernandes, Pedro Dantas; Rocha, Maria do Socorro (Semina: Ciências Agrárias, 2014)
The objective of this study was to evaluate gas exchange and photochemical efficiency of cotton cultivars under leaf application of silicon. Therefore, the experiment was conducted in a completely randomized in a factorial 3 x 5, three cotton cultivars ('BRS Topázio', 'BRS Safira' and 'BRS Rubi'), five silicon concentrations (0, 50, 100, 150, 200 mg L-1) and four replications. Gas exchange and photochemical efficiency were determined by measuring the rate of CO2 assimilation, transpiration, stomatal conductance, internal CO2 concentration, instantaneous efficiency in water use, instantaneous carboxylation efficiency, initial fluorescence, maximum quantum efficiency of the variable and photosystem II (PSII). The data variables were subjected to analysis of variance and regression test comparison of means. There were significant differences in gas exchange and photochemical efficiency in response to concentrations of silicon. There were also significant differences among cotton cultivars evaluated. In cultivar 'BRS Topázio', the application of silicon increased CO2 assimilation rate and quantum efficiency of PSII. In 'BRS Safira' silicon reduced the rate of assimilation and internal CO2 concentration. In 'BRS Rubi' element increased the fluorescence of chlorophyll 'a' and quantum efficiency of photosystem II, and reduced the rate of assimilation and internal CO2 concentration and stomatal conductance. Silicate fertilization provided 'BRS Topázio' to express better photosynthetic rate in relation to 'BRS Safira' and 'BRS Rubi'. No damage occurred in PSII when 'BRS Topázio', 'BRS Safira' and 'BRS Rubi' cultivars received silicon as supplementary nutrition.